Implementasi Perizinan Pendirian Rumah Ibadah Kota Surabaya - Handoyo, Muhammad Akbar Putra; Singgih Manggalou (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is motivated by how the licensing of the construction of houses of worship to the applicant, this research needs to be done to find out how the implementation of licensing the establishment of houses of worship in the city of Surabaya through various stakeholders such as FKUB, KEMENAG, BAKESBANGPOL, and DPRKPP. The theory used in this research is the implementation theory of Marilee S. Grindle and this theory is measured by two dimensions and nine indicators. The policy content dimension has indicators including the interests that influence, the type of benefits, the degree of change to be achieved, the location of decision making, program implementation, and the sources of resources used. The implementation environment dimension includes three indicators including the power, interests and strategies of the actors involved, the characteristics of the ruling institutions and regimes, and the level of compliance and response from implementers. This research uses a qualitative descriptive method. The results showed that the implementation of licensing for the establishment of houses of worship in Surabaya City can be said to be less successful, this is indicated by 99 houses of worship that get recommendations but only 3 places of worship that take care of their IMB, where 2 worship services have obtained IMB status and 1 house of worship needs to take care of the files to be re-submitted.